2002
DOI: 10.1089/108729002753670256
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Gene Cleavage in Intact Mammalian Cells by 125I-Labeled Triplex-Forming Oligonucleotides Conjugated with Nuclear Localization Signal Peptide

Abstract: Triplex-forming oligonucleotides (TFO) are designed to bind sequence specifically to their DNA targets without a significant disturbance of the double helix. They have been proposed to deliver DNA-reactive agents to specific DNA sequences for gene targeting applications. We suggested the use of 125I-labeled TFO for delivery of the energy of radioiodine decay to specific genes. This approach is called antigene radiotherapy. Here we demonstrate the ability of 125I-labeled TFO to produce sequence-specific breaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Peptides, in particular, are an increasingly popular choice for conjugation with oligonucleotides because of their ability to aid in targeting specific biological functions while improving permeability through the cell membrane and stability against intracellular degradation. Peptide-oligonucleotide conjugates (POCs) have been used to target mRNA, double-stranded DNA, and proteins, in antisense, triple-helix, and aptamer-based therapy, respectively [35]. Our group has recently explored another use of POCs by incorporating peptides used in artificial biomineralization [68] into self-assembling DNA nanostructures [911] for the demonstration of controlled biomineralization [12].…”
Section: Introductionmentioning
confidence: 99%
“…Peptides, in particular, are an increasingly popular choice for conjugation with oligonucleotides because of their ability to aid in targeting specific biological functions while improving permeability through the cell membrane and stability against intracellular degradation. Peptide-oligonucleotide conjugates (POCs) have been used to target mRNA, double-stranded DNA, and proteins, in antisense, triple-helix, and aptamer-based therapy, respectively [35]. Our group has recently explored another use of POCs by incorporating peptides used in artificial biomineralization [68] into self-assembling DNA nanostructures [911] for the demonstration of controlled biomineralization [12].…”
Section: Introductionmentioning
confidence: 99%
“…103 Targeted radiotherapy with oligonucleotide has been proposed by using sequence specific triplex forming oligonucleotides carrying Auger-electron-emitters such as iodine-125 104 to induce localised radio damage to specific sites in the genome. 105 Oligonucleotides as immune modulators The immune stimulation induced by specific oligonucleotide sequences containing unmethylated CpG motifs has already been mentioned. The induction of an immune response by oligonuclotides may find useful applications to protect against infection or trigger immunotherapeutic responses for cancer, allergic or non-conventional infectious diseases.…”
Section: Other Applications Of Oligonucleotidesmentioning
confidence: 99%
“…Further evidence of the ability of TFOs to bind to target sequences within living cells comes from the ability of TFOs to mediate mutagenesis at the target site in yeast cells (Barre et al, 2000), cultured mammalian cells (Vasquez et al, 1999(Vasquez et al, , 2001Wang et al, 1996), and mice (Vasquez et al, 2000). TFO binding to the target sequence in intact mammalian cells was also demonstrated by site-specific, TFO-directed strand cleavage (Sedelnikova et al, 2002). Although mutagenesis or cleavage events are infrequent, they have unambiguously demonstrated that a TFO can bind to a target sequence in living Arizona Cancer Center,Tucson,AZ 85724. cells.…”
Section: Introductionmentioning
confidence: 99%